Огляд проблем ефективного використання паливно-енергетичних ресурсів в промисловому секторі України та можливі оптимальні шляхи їх вирішення - Кавєрцєв, Валерій Леонідович; Дягілєв, Вадим Олександрович (НТУ "ХПІ", 2017)
Розглянуті актуальні питання щодо проблеми ефективного використання та споживання паливно-енергетичних ресурсів в промисловості Україні. Наведенні приклади пошуку технічних рішень, які можуть знизити собівартість теплової та електричної енергії. Наведені статистичні дані використання паливнo-енергетичних ресурсів у найбільш енерговитратних галузях промисловості. У висновках вказані причини неефективного викорис-тання енергоресурсів і запропоновані рекомендації щодо доцільного їх використання шляхом побудови нових або модернізації діючих енергетичних установок.

The purpose of this scientific paper was to analyze actual problems related to the use of fuel and power resources and faced today by the power economy sector in Ukraine. An efficient use of these resources provides a stable power supply for the State. At the present time Ukraine survives a considerable rise in price for natural gas and other traditional power resources. This scientific paper describes the basic measures taken to decrease the cost price of used power resources and reduce the amount of expensive fuel used byindustrial companies in Ukraine. This paper gives the statistics of the use of fuel and power resources by the companies of mining and smelting sector that are the key consumers of power resources. It should be noted in conclusion that Ukraine has a considerable potential for the reduction of the consumption of fuel and power resources due to the optimized use of secondary power resources through the manufacture of new boilers and the modernization of old boiler units that would enable the combustion of the fuels of a wide range. The wanted effect can be achieved through the improvement of firing burners installed in the boilers.
Reviewing an efficiency of the use of fuel and power resources for the industry of Ukraine
Keywords: енергетика; енергозабезпечення; види палива; природний газ; вторинні енергоресурси; доменний газ; коксовий газ; power engineering; power supply; fuel types; natural gas; secondary power resources